Uma sequência de ensino investigativa em bioquímica de alimentos - Fabio Alexandre Santos Lima (2020)
This Master's Completion Work consists of an investigative teaching sequence in Food Biochemistry, aimed at promoting adequate and healthy eating in basic education, especially in high school. The right to adequate and healthy food is legally foreseen in the following legislations, namely: a) Federal Constitution of 1988; b) in the National Food and Nutrition Policy, which aims to improve food, nutrition and health conditions for the Brazilian population; c) in the National School Feeding Program, which guaranteed the supply of food in schools as a right of students, as well as a duty of the State; d) in Law 11.947/2009, which aims to contribute to growth and biopsychosocial development, learning, school performance and the formation of healthy eating habits among students; e) in Law No. 9,394/1996, which defined the curricula of education systems and networks, as well as the pedagogical proposals of all Brazilian schools, with food and nutrition education included among the cross-cutting themes dealt with in this law; f) in the National Curriculum Parameters. The main objective of the TCM is to promote and evaluate the learning of basic concepts in Food Biochemistry, while the specific objectives intended to discuss the composition and nutritional variety of the student's daily foods, as well as their association with energy production and body building activity. , encouraging youth to play a leading role through their participation in choosing and suggesting a healthier school food menu. This work is divided into three stages, namely: (1) previous questionnaire; (2) Investigative Teaching Sequence (SEI); (3) post-SEI questionnaire. It was found that students have knowledge about the composition and variety of nutrients present in their daily school foods, as well as signaled by those that the carbohydrate nutrient is the main nutrient responsible for generating energy in the combustion of food, as mentioned that other nutrients are co-responsible for generating energy from food. On the other hand, students were unaware or did not consider the importance of the constructive role played by proteins in the body of living beings, and they also had difficulties in understanding the scientific meaning of the term calorie. It is concluded that the use of this theme through teaching by investigation enabled an association between the conceptual aspects of the discipline of Science, as well as used the prior knowledge that students have of their daily lives, allowing the elaboration and testing of hypotheses as well as the individual and collective systematization of knowledge, thus providing an improvement in the teaching-learning process in food biochemistry.